Individualisme Melunturkan Nilai-Nilai Pancasila - Mukhbita Alya; Putri Wulandari; Dinda Rezika Shifa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The attitude of selfishness or what we usually know as individualism is one of the main factors in the erosion of Pancasila values. The attitude of individualism is always present in the social environment. One of the main factors in the emergence of individualism in society is globalization. The increasingly rapid development of technology means that people can do everything without interacting directly. Apart from that, the attitude of individualism is also caused by the influx of western culture without being filtered first. This causes changes in thought patterns, lifestyle and daily living behavior. Individualism has a very negative impact if no one minimizes this attitude. People who are individualistic tend not to be able to work together in groups and lose a sense of solidarity with each other. Therefore, as individuals who are part of society, we have a responsibility to carefully filter and select information in the current context of globalization, for the sake of preserving the fundamental values ​​of Pancasila